METHODOLOGY FOR BUILDING A DIGITAL MODEL OF LAND USE RELIEF USING GEOINFORMATION SYSTEMS - Ryzhok З. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
A digital relief model (FRM) is defined as a digital and mathematical representation of the terrain based on a discrete set of starting points, which allow to reproduce its real surface and structure with a given accuracy. The research uses geoinformation systems Google Earth Pro and ArcGIS 10.2.1 to generate information from the DRM to calculate slope angles and exposure of slopes, the shape of slopes due to the curvature of their transverse and longitudinal sections on the example of model land use. Information about the relief for model land use, located outside the village ща Yampil of Murovanу village council of еру territorial community of Lviv district, Lviv region, with an area of 6.775 hectares for farming was obtained using the Google Earth Pro geoinformation system. The terrain profile of the model land use is plotted, showing that its distance range is 9.95 km, where the minimum elevation is 247 m, the average elevation is 250 m, and the maximum elevation is 253 m. The rise/fall of the terrain corresponds to a value of 50.1/- 50 m, and the maximum slope of the surface is 3.8 and -4.0 % with an average value of 0.8 and -0.9 %. GPS Visualizer, an online utility that helps create maps and profiles from geographic data, is used to display the DEM of model land use in the ArcGIS geoinformation program. In the geoinformation program ArcGIS, a sequence of actions on using the file conversion tool in GPS format, obtained when using GPS Visualizer and based on data of the KMZ type from Google Earth Pro, was performed to construct the DRM of model land use. The Spline with Barries tool is used, which allows displaying the smallest height value – 246.95 m and the largest – 253.10 m for the model land use.